Desenvolvimento de uma vacina bivalente contra linfadenite caseosa e toxoplasmose para pequenos ruminantes. - Flávia de Souza Rocha (2016)
The sheep and goat farming in Brazil has created new business opportunities and become quite significant through implementation of extensive creations farms. Despite the development of new technologies and models of production systems, the sheep and goat industry has been affected by improper handling and by the occurrence of infectious diseases, among which stand out caseous lymphadenitis (LC) and toxoplasmosis - etiological agents Corynebacterium pseudotuberculosis and Toxoplasma gondii, respectively. Both diseases are spread worldwide, and have high prevalence rates, toxoplasmosis being the most widespread type zoonotic disease in the world. Vaccination would be the most appropriate strategy to control and even to eradicate chronic infectious diseases and intensive research has been conducted in this regard. Recently, our research group has shown that a live attenuated vaccine based on CP13 strain of C. pseudotuberculosis (deficient to acquire iron) gives mice 80% protection after challenge with virulent strain. In this context, our goal is to change the vaccine strain CP13 in order to make it a vehicle for the delivery of the immunodominant antigen of T. gondii SAG2 (Surface Antigens), whose protective role against toxoplasmosis has been shown by different research groups. Accordingly, this proposal allows for the view to create a bivalent vaccine against toxoplasmosis LC and a low production cost and possibility of a single dose administration. By using different plasmids heterologous expression in corynebacteria, we were able to obtain three different lines derived from that produced CP13 antigen rSAG2 constitutively or induced by IPTG. The expression levels of the heterologous protein by CP13 strain were evaluated by SDS-PAGE, however low levels of the translated protein was detected in the strain transformed with the recombinant plasmid constituível promoter, thereby requiring further investigation. The study of infection with recombinant strains in murine model was accomplished and as a result, we observed reduction in virulence and persistence of all lineages. The data obtained to corroborate the use of these strains as live attenuated vaccine. This study is a first step towards in development of a live attenuated vaccine coupled to an array of heterologous protein expression.